Early Pain Catastrophizing Exacerbates Impaired Limb Loading and 6-Minute Walk Test Distance 12 Months After Lower Extremity Fracture. Issue 11 (14th August 2021) - Van Wyngaarden, Joshua J; Archer, Kristin R; Spencer, Alex; Matuszewski, Paul E; Brightwell, Benjamin; Jacobs, Cale; Noehren, Brian
Abstract: Objective: Disability is common after lower extremity fracture (LEF). Although psychosocial factors have been associated with patient-reported outcomes after LEF, they have not been associated with objective measures of function. Aberrant gait patterns are important markers of function, but are poorly defined after LEF. The primary purpose of this study was to explore whether pain catastrophizing and fear of movement 6 weeks after surgery were associated with injured limb loading outcomes and 6-minute walk test (6MWT) distance 12 months after femur or tibia fracture. The secondary purpose was to determine if limb loading characteristics differed between injured and uninjured limbs. Methods: At 6 weeks after LEF, patients completed validated measures of pain catastrophizing, fear of movement, and depression. At 12 months, patients completed a 6MWT while wearing instrumented insoles that recorded the limb loading outcomes of stance time, impulse, and loading rate. Bivariate correlations assessed how patient and psychosocial characteristics at 6 weeks were associated with injured limb loading outcomes and 6MWT distance. Multivariable regression analyses were performed to determine if psychosocial variables were associated with each outcome after controlling for depression and patient demographic and clinical characteristics. Finally, paired t tests compared limb loading outcomes between limbs. Results: Forty-seven participants completed the 6MWT at 12 months (65%), and 38 completed the 6MWT with the instrumented insoles. Fear of movement carried a poor relationship ( r  = 0.11–0.32) and pain catastrophizing a moderate relationship ( r  = 0.46–0.54) with 12-month outcomes. The regression results indicated that pain catastrophizing continued to be associated with all outcomes. Finally, the injured limb had significantly lower limb loading outcomes than the uninjured limb at 12 months (Cohen d  = 0.54–0.69). Conclusion: Pain catastrophizing early after LEF was associated with impaired limb loading and 6MWT distance at 12 months. Impact: Impaired limb loading persists 12 months after LEF. Further research is needed to determine whether rehabilitative efforts focused on pain catastrophizing can restore limb loading after LEF.